THE WEYL TRANSFORM OF A SMOOTH MEASURE ON A REAL-ANALYTIC SUBMANIFOLD - Mishra M.; Vemuri M.K. (My University, 2025)
If μ is a smooth measure supported on a real-analytic submanifold of R2n which is not contained in any affine hyperplane, then the Weyl transform of μ is a compact operator. © The Author(s), 2024.